Pendampingan penguatan manajemen dan akuntansi bagi UMKM melalui legalitas NPAK menjadi badan hukum koperasi - Utomo, Sulistyo Budi; Dewi, Mega Arisia; Sidharta, R. Yudi; Suprihhadi, Heru; Widiarma, Inam (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The establishment of cooperatives is inseparable from the role of the Cooperative Deed Drafting Notary (NPAK), an authorized official responsible for drafting cooperative establishment deeds. Through legal recognition as a legal entity, NPAK provides specialized services in drafting cooperative deeds, which cannot be performed by general notaries. Cooperatives play a strategic role in empowering micro, small, and medium enterprises (MSMEs) to improve members' welfare and strengthen management and accounting practices to ensure business operations align with their objectives. This activity involved guidance by NPAK in collaboration with Dekopinda Surabaya City on the importance of establishing cooperatives for MSMEs. The stages included comprehensive assistance in the application, drafting, and signing of cooperative establishment deeds and the subsequent approval process. The results indicated that the cooperative establishment process for MSME members in Surabaya City was successfully implemented, providing significant benefits in enhancing members' welfare